The end of the Russian Imperial Army : the old Army and the soldiers' revolt (March-April, 1917) - Wildman, Allan K. (Princeton legacy library., 1980)
Allan Wildman presents the first detailed study of the Army's collapse under the strains of war and of the front soldiers' efforts to participate in the Revolution. Originally published in 1980. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase.